2017
DOI: 10.1093/carcin/bgx054
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a promising agent to treat ovarian cancer: molecular mechanisms

Abstract: Ovarian cancer (OC) has the highest mortality rate of all gynecological cancers, and most patients develop chemoresistance after first-line treatments. Despite recent advances, the 5-year relative survival is ~45% for all OC subtypes, and invasive epithelial OC has only a 17% survival rate when diagnosed at a late stage. Identification of new efficacious molecules or biomarkers represents important opportunities in the treatment of OC. The pharmacological and physiological properties of melatonin indicate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 82 publications
0
58
0
Order By: Relevance
“…Pathological inflammation has been related to several different diseases, and current anti-inflammatory drugs have significant side effects; so, it is important to identify new therapeutic approaches to reduce inflammatory processes without impairing the physiologic inflammatory response. As reported above, melatonin has many actions [ 14 , 37 , 43 , 87 89 ] and numerous experimental studies have shown that melatonin is not only an important antioxidant but also a widespread anti-inflammatory molecule [ 45 , 82 , 88 , 90 92 ]. Thus, melatonin is a molecule of high clinical interest.…”
Section: Melatonin and Inflammationmentioning
confidence: 99%
“…Pathological inflammation has been related to several different diseases, and current anti-inflammatory drugs have significant side effects; so, it is important to identify new therapeutic approaches to reduce inflammatory processes without impairing the physiologic inflammatory response. As reported above, melatonin has many actions [ 14 , 37 , 43 , 87 89 ] and numerous experimental studies have shown that melatonin is not only an important antioxidant but also a widespread anti-inflammatory molecule [ 45 , 82 , 88 , 90 92 ]. Thus, melatonin is a molecule of high clinical interest.…”
Section: Melatonin and Inflammationmentioning
confidence: 99%
“… Borin et al (2016) observed similar results in vitro human breast cancer cell lines MDA-MB-231 (metastatic, ERα-negative). Furthermore, melatonin has been shown to convert the human breast cancer cell line MCF-7 to a less invasive phenotype by increasing expression of E-cadherin, a prototypical member of the type-1 classical cadherins whose loss favors tumor metastasis ( Cos et al, 1998 ; Chuffa et al, 2017 ). The anti-invasive effect of melatonin on breast cancer may be also through the downregulation of the p38 pathway and suppression of metalloproteinases-2 and -9 expression and activity ( Mao et al, 2010 ).…”
Section: Melatoninmentioning
confidence: 99%
“…Ovarian cancer occurs in women with a prevalence ~15,000 per 100,000 individuals worldwide (20). Due to a lack of specific symptoms in the early stages, 60-70% of patients with ovarian cancer are diagnosed at an advanced stage, and their 5-year survival rate is ~40% (21,22). Standard therapy strategies for advanced-stage ovarian cancer are primary debulking surgery combined with platinum and paclitaxel chemotherapy (23,24).…”
Section: Introductionmentioning
confidence: 99%